2015
DOI: 10.3389/fpls.2015.01067
|View full text |Cite
|
Sign up to set email alerts
|

Production of the Main Celiac Disease Autoantigen by Transient Expression in Nicotiana benthamiana

Abstract: Celiac Disease (CD) is a gluten sensitive enteropathy that remains widely undiagnosed and implementation of massive screening tests is needed to reduce the long term complications associated to untreated CD. The main CD autoantigen, human tissue transglutaminase (TG2), is a challenge for the different expression systems available since its cross-linking activity affects cellular processes. Plant-based transient expression systems can be an alternative for the production of this protein. In this work, a transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Here, we showed that a mouse IgG accumulated at increased yields in leaf central vacuole indicating low‐Ab‐related proteolytic activities in this compartment. Similar results were reported for human α‐mannosidase (De Marchis et al ., ), human complement factor C5a, (Nausch et al ., ), collagen (Stein et al ., ), human α1‐proteinase inhibitor (Jha et al ., ) and human transglutaminase 2 (Marin Viegas et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, we showed that a mouse IgG accumulated at increased yields in leaf central vacuole indicating low‐Ab‐related proteolytic activities in this compartment. Similar results were reported for human α‐mannosidase (De Marchis et al ., ), human complement factor C5a, (Nausch et al ., ), collagen (Stein et al ., ), human α1‐proteinase inhibitor (Jha et al ., ) and human transglutaminase 2 (Marin Viegas et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Retention of Abs in the endoplasmic reticulum (ER) frequently results in increased yields (De Muynck et al ., ). Although the plant central vacuole is considered a hostile environment for foreign protein accumulation, it has been shown that some proteins, such as human alpha‐mannosidase (De Marchis et al ., ), human complement factor C5a, (Nausch et al ., ), collagen (Stein et al ., ) and human transglutaminase 2 (Marin Viegas et al ., ), accumulate in this organelle. In contrast, in carrot suspension cell cultures, secretory versions of human IgG1 and G4 have higher yields than ER and vacuolar variants (Shaaltiel et al ., ).…”
Section: Introductionmentioning
confidence: 94%
“…tumefaciens transient expression system to accelerate the development of a malaria vaccine candidate, with screens for expression, solubility, and stability using fluorescent fusion proteins. In Marin Viegas et al [60], a transient expression system for the production of human TG2 in N. benthamiana leaves was optimized, and the reactivity of plant-produced TG2 in a CD screening test was evaluated. Hence, transient expression performed in contained facilities satisfies good manufacturing practices, and quick expression can avoid the time-consuming stable transformation [58,61].…”
Section: Plant-based Expression System For Vaccine Developmentmentioning
confidence: 99%
“…The type of cell compartment in which they are found directly influences the folding, assembling, and posttranslational modifications processes, as well as preventing immediate degradation and interference of the polypeptides with cell metabolism (Ahmad et al, 2010;Leite et al, 2019). Typically, the main compartments to which recombinant proteins are targeted include the apoplast, the vacuole, the endoplasmic reticulum, the chloroplasts, and the cytosol (Pereira el at., 2014;Viegas et al, 2015;Miletic et al, 2016) It has also been shown that adding fusion tags, such as elastinlike polypeptides (ELP), hydrophobins (HFBI), and Zera (an Nproline-rich region of gamma zein) to recombinant proteins increases their levels of accumulation. In general, ELP fusions increased the production yield of these target proteins by 2-to 100-fold (Conley et al, 2011) and HFBI fusion led to an increase of GFP accumulation in Nicotiana benthamiana leaves from 18% to 38% of TSP (Joensuu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained using the subcellular targeting strategies or fusion to insoluble tags depend on the nature of the recombinant protein (Viegas et al, 2015). Although other recombinant DENV proteins have been previously targeted to the ER (Seajung et al, 2007;Kim et al, 2009), these strategies have not been tested on the DENV NS1 accumulation in plants.…”
Section: Introductionmentioning
confidence: 99%